HUBUNGAN SUPERVISI KEPALA RUANGAN TERHADAP PELAKSANAAN KOMUNIKASI SBAR PADA SAAT HANDOVER - Harry Permana Wibowo; Basri Basri; Afeus Halawa (Jurnal Keperawatan Priority, 2022)
Communication is the most important thing in providing services to patients because everything related to Covid-19 patients must be conveyed, well, and correctly. On this basis, adjustments are needed from various parties to communicate so that the message to be conveyed regarding patients can run smoothly. Until now this continues to be a concern of all medical personnel and adjustments are needed in communicating considering the obstacles experienced. This study used a cross-sectional design. The location of research was held at Bhayangkara General Hospital, Banda Aceh. Sampling technique with random sampling with a sample of 57 patients. Data collection using the observation table instrument. The statistical test used the Chi-square test. The majority of room head supervision is in the good category 55 people (96.5%). The results of the study obtained were that the majority of nurses' SBAR communication was good as many as 54 people (94.7), and the relationship between the two variables between the implementation of supervision of the head of the room and the implementation of SBAR communication obtained the p-value of 0.000. Suggestions in this study are expected to be the basis for hospital management policy to improve hospital services, especially in terms of implementing the supervision of the head of the room and the implementation of nurse SBAR communication. This research can play a major role in terms of providing nursing services in the future. The increase in nursing communication services can reduce unwanted events.